EFFECT OF LIME AND CELLULOSE TREATMENT ON DEACIDIFICATION OF ACID-SULPHATE SOILS DURING INUNDATION UNDER LABORATORY CONDITIONS - Abdul Karim Gaffar (Research Center for Fisheries, 1995)
An experiment was conducted to assess the effects of lime and cellulose additions ondeacidification of submerged ecid sulphate soil in laboratory condition for 6 weeksduration.